Foreign Acquisitions and Target Firms' Performance in China. (12th August 2016) - Liu, Qing; Lu, Ruosi; Qiu, Larry D.
Abstract: This paper empirically investigates the effects of foreign acquisitions on several performance measures of Chinese target firms. Using a self‐constructed database that includes information on foreign acquisitions in China and the accounting information of Chinese manufacturing firms from 1998 to 2007, we find that foreign acquisitions significantly improve the productivity, sales and fixed asset investment of the target firms. We address the potential endogeneity issue in the OLS estimation using the difference‐in‐differences technique, with two control groups, namely the would‐be targets and the propensity‐score‐matched targets. We also find that the performance‐enhancing effect of foreign acquisitions becomes stronger when larger technology gaps are observed between the acquirers and the targets. An inverted‐U relationship is observed between the post‐acquisition performance of the target firms and the target firm equity that is held by the foreign acquirers. The performance effects are qualitatively different among vertical, horizontal and conglomerate acquisitions.